1998
DOI: 10.1007/s007010050126
|View full text |Cite
|
Sign up to set email alerts
|

Altered Excitability of the Motor Cortex after Minor Head Injury Revealed by Transcranial Magnetic Stimulation

Abstract: This study attempts to find out whether the motor evoked potential (MEP) elicited by single pulse and slow-rate (1 Hz) repetitive transcranial magnetic stimulation (TMS) can disclose concealed subclinical impairments in the cerebral motor system of patients with minor head injury. The motor response to single pulse TMS (STMS) of the patient group was characterized by significantly higher threshold compared with that of the control group. The central motor conduction time, as well as the peripheral conduction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
4
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 8 publications
2
17
4
1
Order By: Relevance
“…While this hypothesis is based on studies in M1 nTMS (see Introduction), similar relation with peak latency and balance of inhibition-facilitation could be expected on DLPFC. Our findings would also be compatible with previous TMS studies in mTBI, where acutely decreased M1 excitability 17,18 and a persistently prolonged cortical silent period have been found, 41 suggesting lowered excitability and a stronger inhibitory response.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While this hypothesis is based on studies in M1 nTMS (see Introduction), similar relation with peak latency and balance of inhibition-facilitation could be expected on DLPFC. Our findings would also be compatible with previous TMS studies in mTBI, where acutely decreased M1 excitability 17,18 and a persistently prolonged cortical silent period have been found, 41 suggesting lowered excitability and a stronger inhibitory response.…”
Section: Discussionsupporting
confidence: 93%
“…12,15 Higher rMT has previously been associated with TBI of varying severity, [16][17][18] possibly also correlating with recovery, at least in mild injuries. 17 nTMS-evoked electroencephalographic responses (nTMS-EEG) can be used to study cortical excitability and connectivity. In nTMS-EEG, certain individually highly reproducible deflections are found, including P30, N45, P60, N100, and P200.…”
Section: Introductionmentioning
confidence: 97%
“…For the detection of the failure of corticospinal tract conduction, the triple stimulation technique, which consists of one transcranial magnetic and two peripheral electric stimuli (plexus and nerve) delivered along the motor pathways, might have higher sensitivity than conventional MEP or CMCT testing [64]. In contrast to these results, a higher RMT is reported in patients with moderate focal TBI, while no difference was found between patients with minor or moderate diffuse TBI [13,19]. The authors have also described some improvement in the observed high RMT in the three-months follow-up study [19].…”
Section: Discussioncontrasting
confidence: 51%
“…In contrast to these results, a higher RMT is reported in patients with moderate focal TBI, while no difference was found between patients with minor or moderate diffuse TBI [13,19]. The authors have also described some improvement in the observed high RMT in the three-months follow-up study [19]. Our findings of normal RMT in brain injury patients could firstly be explained by that fact, that the period after the insult was longer in our study (on average 4 months); secondly, that the majority of the included patients suffered from a non-traumatic brain injury with possibly less pronounced axonal damage.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation